The impact of the war in Ukraine on the prevalence of MDR/RR-TB in Poland - A. Nowinski; E. Augustynowicz-Kopeć; J. Garnczarek; A. Halicka; M. Koszela; W. Litwiniuk; D. Maj; I. Mazur; J. Niestrój-Ostrowska; R. Podlasin; A. Regulska; M. Wielopolska; et al. (IJTLD Open)
BACKGROUND: The 2022 invasion of Ukraine by the Russian Federation triggered a refugee crisis, affecting the multidrug-/rifampicin-resistant TB (MDR/RR-TB) prevalence in neighbouring countries. This study examines the epidemiological trends and characteristics of MDR/RR-TB patients in Poland, focusing on the relative contribution of Ukrainian refugees. METHODS: Data from the Polish National Tuberculosis Registry and EPIC Project database, covering MDR/RR-TB cases reported between 2010 and Q1 2024, were analysed. RESULTS: The study included 794 MDR/RR-TB cases, showing a demographic shift post-2022. During the 10-year period up to 2021, a median of 48 MDR/RR-TB cases were reported annually in Poland. After 2022, these numbers doubled: 104 cases were reported in 2022 and 101 cases in 2023. Simultaneously, the number of Ukrainian MDR/RR-TB patients increased from 77 (13%) during 2010–2021 to 127 (58%) from 2022 to Q1 2024. CONCLUSION: Poland is observing an increased number of cases of MDR/RR-TB associated with the large number of displaced Ukrainian citizens who are now residing in Poland. There is a need to monitor the epidemiology of MDR/RR-TB and seek optimal screening and management strategies for TB among refugees from countries with high MDR/RR-TB incidence in Poland and Europe.